Implementasi Web Server Load BalancingPada Mesin Virtual - Yoga Hartomo, Handoko; , Ir.Bana Handaga, MT., Ph.D (2015)
Rapid technological development, making the need for communication and information become a staple of everyday life. More and more people are accessing information through the Internet, causing the web server to work harder and less than optimal performance. Merging multiple servers (clusters) with Load Balance technique, can be used to overcome these problems because this technique works by dividing the load received by the server and when one server fails, then the other cluster members will server requests from the client. This study aims to create a web server with Load Balance technique on the virtual machine. Applications used in this study is VMware, Ubuntu Server 14:10, Pound, HAProxy, and Webserver Stress Tool 8. This experiment is availability testing, and testing using Webserver Stress Tool 8. From the test Availability, web server cluster members can actively serve client when one of the web server failure. Of testing with Webserver Stress Tool 8, the average response time on the Pound and HAProxy Load Balancer show different results. Based on testing using the Web Server Stress Tool 8, the average response time on HAProxy showed a faster response time than the Pound. And the speed of data transfer on HAProxy showed a faster pace than the Pound. Keyword : Cluster, Load Balance, Virtualization, Web Server.